Viscoelastic Testing in Pediatric Mechanical Circulatory Support - Regling, Katherine; Saini, Arun; Cashen, Katherine (Frontiers in Medicine, 2022)
Pediatric mechanical circulatory support can be lifesaving. However, managing anticoagulation is one of the most challenging aspects of care in patients requiring mechanical circulatory support. Effective anticoagulation is even more difficult in pediatric patients due to the smaller size of their blood vessels, increased turbulent flow, and developmental hemostasis. Recently, viscoelastic testing (VET) has been used as a qualitative measure of anticoagulation efficacy in patients receiving extracorporeal membrane oxygenation (ECMO) and ventricular assist devices (VAD.) Thromboelastography (TEG®) and thromboelastometry (ROTEM®) provide a global qualitative assessment of hemostatic function from initiation of clot formation with the platelet-fibrin interaction, platelet aggregation, clot strength, and clot lysis. This review focuses on the TEG®/ROTEM® and important laboratory and patient considerations for interpretation in the ECMO and VAD population. We summarize the adult and pediatric ECMO/VAD literature regarding VET values, VET-platelet mapping, utility over standard laboratory monitoring, and association with outcome measures such as blood product utilization, bleeding, and thrombosis.